Seed Yield Enhancement Techniques in Fodder Maize (Zea mays L.) - KL RAVI KUMAR,; VINOD KUMAR,; BS VYAKARNAHAL,; BB CHANNAPPAGOWDAR,; MC WALI, (Seed Research, 2026)
A field experiment was conducted at Main Agricultural Research Station, University of Agricultural Sciences, Dharwad, during kharif 2014, to evaluate seed yield enhancement techniques in fodder maize (cv. African Tall). The experiment was laid out in simple RCBD with 10 treatments replicated thrice. The results of the investigation revealed that highest field emergence, minimum days to 50 per cent tasseling, 50 per cent silking and days to maturity was recorded in seeds primed with KH2PO4 (2%) + polymer coating @3 ml per kg of seed (95.38%, 64.33, 70.33 and 117.00, respectively). Among different seed yield enhancement techniques, seed treatment with zinc sulphate (ZnSO4) @ 2 g per kg of seed + polymer coating @ 3 ml per kg of seed + soil application of zinc sulphate (ZnSO₄) @ 10 kg per ha recorded significantly highest plant height at harvest (297.80 cm), dry matter production at harvest (244.27 g) and maximum yield parameters viz., maximum cob length (19.15 cm), cob girth (16.10 cm), number of seeds per row (36.22), number of seeds per cob (482.00), cob weight (171.37 g), seed yield per ha (34.54 q) and test weight (33.04 g).